2009
DOI: 10.1007/s10539-009-9155-0
|View full text |Cite
|
Sign up to set email alerts
|

Guessing the future of the past

Abstract: I review the book ''Making Prehistory: Historical Science and the Scientific Realism Debate'' by Derek Turner. Turner suggests that philsophers should take seriously the historical sciences such as geology when considering philosophy of science issues. To that end, he explores the scientific realism debate with the historical sciences in mind. His conclusion is a view allied to that of Arthur Fine: a view Turner calls the natural historical attitude. While I find Turner's motivations good, I find his character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Studying the history of life on earth requires drawing reliable inferences about past organisms, events, and processes from present day traces, including molecules in living organisms (Easteal et al 1995). Progress in understanding the past is limited by the available traces, but the history of science has shown that at any given time, it simply cannot be known what traces will prove to be evidentially relevant (Jeffares 2010). Inferences about the past must be indemnified against certain sorts of risks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying the history of life on earth requires drawing reliable inferences about past organisms, events, and processes from present day traces, including molecules in living organisms (Easteal et al 1995). Progress in understanding the past is limited by the available traces, but the history of science has shown that at any given time, it simply cannot be known what traces will prove to be evidentially relevant (Jeffares 2010). Inferences about the past must be indemnified against certain sorts of risks.…”
Section: Resultsmentioning
confidence: 99%
“…If so, what is the best way to characterize them? For philosophers who have turned their gaze to paleontology, a consensus has emerged that the key to understanding its epistemic challenges involves grappling with the underdetermination of theory by data (Cleland 2002;Turner 2007;Jeffares 2010;Forber 2009;Forber andGriffith 2011). Carol Cleland (2002) set the terms of the debate by invoking a pervasive time asymmetry of nature that historical sciences such as paleontology exploit in drawing causal inferences.…”
Section: Epistemic Access To the Past: The Colors Of The Dinosaursmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of focus on sciences that do not rely on experimental methods has led philosophers of science (Brown, 2011;Cleland, 2002;Jeffares, 2009;Tucker, 2011;Turner, 2007) and scientists themselves (Diamond, 1997;Erwin, 2011;Gould, 1986;Mayr, 1985;Schumm, 1991) to more thoroughly examine the historical sciences. While the discussion over what truly separates these two modes of science continues, some areas of consensus have emerged.…”
Section: Defining Two Modes Of Scientific Inquirymentioning
confidence: 99%
“…Jeffares (2010) provides many reasons to resist such skepticism, for our apparent access to the past continues to improve. To take a single telling example, Turner (2007) cites the coloration of dinosaurs as an illustration of an unanswerable question about the past.…”
Section: The Problem Of Accessmentioning
confidence: 99%